Turkey at the Crossroads : From Crisis Resolution to EU Accession - McGettigan, Donal; Debrun, Xavier; Griffiths, Mark.; Moghadam, Reza. (Washington, D.C. : International Monetary Fund, 2005)
The key policy challenge for Turkey in the years ahead will be to enhance and consolidate the advances made since the nation's 2000-01 economic crisis. Higher growth could reduce unemployment and raise living standards toward European Union levels. This paper reviews Turkey's policy performance in terms of growth, inflation, debt, fiscal and financial sector reform, and labor markets. The analysis assesses the effectiveness of macroeconomic stabilization and structural reforms since the crisis and provides guideposts for future policy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet